111k views
1 vote
Solve by factoring: X^3+7x^2-x-7=0

Solve by factoring: X^3+7x^2-x-7=0-example-1

2 Answers

7 votes


{x}^(3) + 7 {x}^(2) - x - 7 = 0 \\ \Leftrightarrow {x}^(2) (x + 7) - (x + 7) = 0 \\ \Leftrightarrow ( {x}^(2) - 1)(x + 7) = 0 \\ \Leftrightarrow (x - 1)(x + 1)(x + 7) = 0 \\ \Leftrightarrow x = - 7 \: \vee \: x = - 1 \: \vee \: x = 1

User Ente
by
5.1k points
3 votes

Answer:


\boxed{\bold{\left(x+7\right)\left(x+1\right)\left(x-1\right)=0}}

Explanation:

Factor
\bold{x^3+7x^2-x-7}


\bold{\left(x+7\right)\left(x^2-1\right)}

Factor
\bold{0}


\bold{0}

Rewrite Equation


\bold{\left(x+7\right)\left(x+1\right)\left(x-1\right)=0}

User DreTaX
by
5.8k points